We don't like (to) party : explaining the significance of Independents in Irish political life - Weeks, Liam (Trinity College (Dublin, Ireland). Department of Political Science, 2008)
The aim of this thesis is to explain the significant presence of Independents (non-party representatives) in the Irish political system. This topic was chosen because parties have a monopoly on parliamentary representation in almost all liberal democracies. Ireland is an exception to this pattern, as independents have been elected to every session of parliament since the foundation of the modern Irish state. There have been very few academic analyses of Independents carried out in relation to any political system, and this study therefore makes a significant contribution to the political science discipline. Important contributions are also made to the specific areas of candidate emergence, campaign effects, voting behaviour, and electoral systems. This thesis sheds light on the background on Independent candidates and why they choose to run for office; it provides a detailed analysis of the effects of campaign activities; and it assesses the consequences of an electoral system that has been under-studied.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin